Leukoaraiosis May Confound the Interpretation of CT Perfusion in Patients Treated with Mechanical Thrombectomy for Acute Ischemic Stroke - Rudilosso, S.; Laredo, C.; Vivancos, C.; Urra, X.; Llull, L.; Renú, A.; Obach, V.; Zhao, Y.; Moreno, J.L.; Lopez-Rueda, A.; Amaro, S.; Chamorro, Á. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Leukoaraiosis frequently coexists in patients with acute stroke. We studied whether leukoaraiosis could confound the interpretation of CTP findings in patients treated with mechanical thrombectomy.MATERIALS AND METHODS: We analyzed 236 patients with stroke treated with mechanical thrombectomy and studied with CTP, of whom 127 (53.8%) achieved complete reperfusion. Periventricular white matter hyperintensities on MR imaging and hypodensities on NCCT were assessed through the Fazekas score. CTP-predicted nonviable tissue was defined as relative CBF <30%, and final infarct volume was quantified in DWI. We estimated mean MTT, CBV, and CBF in the asymptomatic hemisphere. In patients achieving complete reperfusion, we assessed the accuracy of nonviable tissue to predict final infarct volume using the intraclass correlation coefficient across periventricular hyperintensity/hypodensity Fazekas scores and variable relative CBF cutoffs.RESULTS: MTT was longer (Spearman ρ = 0.279, P < .001) and CBF was lower (ρ = −0.263, P < .001) as the periventricular hyperintensity Fazekas score increased, while CBV was similar across groups (ρ = −0.043, P = .513). In the subgroup of patients achieving complete reperfusion, nonviable tissue–final infarct volume reliability was excellent in patients with periventricular hyperintensity Fazekas score grade 0 (intraclass correlation coefficient, 0.900; 95% CI, 0.805–0.950), fair in patients with periventricular hyperintensity Fazekas scores 1 (intraclass correlation coefficient, 0.569; 95% CI, 0.327–0.741) and 2 (intraclass correlation coefficient, 0.444; 95% CI, 0.165–0.657), and poor in patients with periventricular hyperintensity Fazekas score 3 (intraclass correlation coefficient, 0.310; 95% CI, −0.359–0.769). The most accurate cutoffs were relative CBF <30% for periventricular hyperintensity Fazekas score grades 0 and 1, relative CBF <25% for periventricular hyperintensity Fazekas score 2, and relative CBF <20% for periventricular hyperintensity Fazekas score 3. The reliability analysis according to periventricular hypodensity Fazekas score grades on NCCT was similar to that in follow-up MR imaging.CONCLUSIONS: In patients with stroke, the presence of leukoaraiosis confounds the interpretation of CTP despite proper adjustment of CBF thresholds.FIVfinal infarct volumeICCintraclass correlation coefficientIQRinterquartile rangeMTmechanical thrombectomyNVTnonviable tissuePVHperiventricular hyperintensity/hypodensity Fazekas scorerCBFrelative CBF